The aeromagnetic expression of New Zealand's Alpine Fault: regional displacement and entrainment of igneous rock. Issue 3 (3rd July 2018) - Rattenbury, Mark S.; Vidanovich, Paul
ABSTRACT: The Alpine Fault is very well delineated by recent high-resolution aeromagnetic data sets over much of its length in New Zealand's South Island. Aeromagnetic data acquired over parts of the West Coast, Tasman and Marlborough regions for the New Zealand Government reveal different types of total magnetic intensity anomalies associated with the fault that can be characterised as truncated, step, ridge, trough and broad anomalies. Fault-terminated Permian ultramafic rocks, Late Cretaceous basalt and some Early Cretaceous intrusions are attributed to the more prominent truncated anomalies. The pre-eminent step anomaly is associated with relatively magnetic Alpine Schist juxtaposed against variable but generally less magnetic Western Province rocks. Strongly positive ridge anomalies occurring in the Alpine Fault zone are associated with Mesozoic mafic metavolcanic and ultramafic rocks. A trough anomaly associated with the Alpine Fault occurs in the southernmost survey and may reflect some hydrothermal demagnetisation. Broad, low-amplitude anomalies underlying the hanging wall are attributed in one instance to the extension of the magnetic Hohonu Range granitoids and dikes extending southeast in the footwall and in other places as magnetic schist rocks in the hanging wall. The apparent great-circle displacement of the Alpine Fault based on offset of magnetic anomalies associated with the Dun Mountain Ultramafics Group rocks is c. 461 km, in close agreement with the more precise 459 km inferred from geological map offset.